2004
DOI: 10.1007/978-3-540-31595-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Collective Motion and Oscillator Synchronization

Abstract: Summary. This paper studies connections between phase models of coupled oscillators and kinematic models of groups of self-propelled particles. These connections are exploited in the analysis and design of feedback control laws for the individuals that stabilize collective motions for the group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 10 publications
(13 reference statements)
0
115
0
Order By: Relevance
“…(1)) where the variables ψ k characterize the lumped behavior of each of the three subgroups. It is assumed that the alignment (orientational) dynamics are independent of the translational counterpart (Sepulchre et al, 2005); hence, the dynamical state of an individual can be characterized by its orientation. The functional form for mutual interaction is borrowed from the well-known Kuramoto model (Kuramoto, 1984), a prototypical model for coupled nonlinear oscillators.…”
Section: A a "Minimal" Model For Identical Individualsmentioning
confidence: 99%
“…(1)) where the variables ψ k characterize the lumped behavior of each of the three subgroups. It is assumed that the alignment (orientational) dynamics are independent of the translational counterpart (Sepulchre et al, 2005); hence, the dynamical state of an individual can be characterized by its orientation. The functional form for mutual interaction is borrowed from the well-known Kuramoto model (Kuramoto, 1984), a prototypical model for coupled nonlinear oscillators.…”
Section: A a "Minimal" Model For Identical Individualsmentioning
confidence: 99%
“…The latest published work returns to this question by deriving the same control laws from a general coordination theory on Lie Groups (Sarlette et al [2010b]). The basic investigation that sustained the underlying research over the seven years interval is the extension of the consensus problem, in which agents dynamically seek a value of common agreement, from values on the real line to values on the circle (Sepulchre et al [2004]). A main reference on this topic is Sarlette and Sepulchre [2009b], strongly supported by the results of the thesis of Sarlette [2009].…”
Section: Introductionmentioning
confidence: 99%
“…In [10] the spontaneous emergence of ordered motion has been studied in terms of so called control laws using graph theory. Generalizations of the control laws were considered in [11,12]. In [12] it was shown that the organized motion of SPP with the control laws depending on the relative orientations of the velocities and relative spacing, can be of two types only: parallel and circular motion.…”
Section: Introductionmentioning
confidence: 99%
“…Generalizations of the control laws were considered in [11,12]. In [12] it was shown that the organized motion of SPP with the control laws depending on the relative orientations of the velocities and relative spacing, can be of two types only: parallel and circular motion. The stability properties of these discrete updating rules (including the T.Vicsek's model) and the dynamics they describe were considered using Lyapunov's theory in [10,11,13,14].…”
Section: Introductionmentioning
confidence: 99%